On the Sanctity of Nature - Kaebnick, Gregory E. (The Hastings Center report, 2000)
Concerns about the sacred—common in everyday moral thinking—have crept into bioethics in various forms. Further, given a certain view of the metaphysics of morals that is now widely endorsed in Western philosophy, there is in principle no reason that judgments about the sacred cannot be part of careful and reasoned moral deliberation.